2013
DOI: 10.1593/neo.13812
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric MEK1/2 Inhibitor Refametinib (BAY 86-9766) in Combination with Sorafenib Exhibits Antitumor Activity in Preclinical Murine and Rat Models of Hepatocellular Carcinoma

Abstract: BAY 86-9766 shows potent single-agent antitumor activity and acts synergistically in combination with sorafenib in preclinical HCC models. These results support the ongoing clinical development of BAY 86-9766 and sorafenib in advanced HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 33 publications
1
42
1
1
Order By: Relevance
“…A similar targeted approach is being taken with the MEK-inhibitor refametinib (BAY 86-9766) in Ras-mutated HCC. Refametinib, a highly selective and potent small molecule allosteric (non-ATP-competitive) inhibitor of MEK 1 and MEK 2, showed potent single agent antitumor activity and acted synergistically in combination with sorafenib in preclinical HCC models, albeit with potential application for only a small subgroup of HCC patients [89][90][91] . Refa- …”
Section: Treatment Of Hccmentioning
confidence: 99%
“…A similar targeted approach is being taken with the MEK-inhibitor refametinib (BAY 86-9766) in Ras-mutated HCC. Refametinib, a highly selective and potent small molecule allosteric (non-ATP-competitive) inhibitor of MEK 1 and MEK 2, showed potent single agent antitumor activity and acted synergistically in combination with sorafenib in preclinical HCC models, albeit with potential application for only a small subgroup of HCC patients [89][90][91] . Refa- …”
Section: Treatment Of Hccmentioning
confidence: 99%
“…15). Sorafenib (Nexavar Ò ; Bayer Pharma AG) is an oral multikinase inhibitor with potent activity against Raf-1 and wild-type and mutant BRAF, and with antiangiogenic activity mediated by inhibition of vascular endothelial growth factor receptors and platelet-derived growth factors (16).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, brivanib, which targets VEGFR, PDGFR and FGFR, also failed to prolong OS (Table 1) in a phase III trial conducted to investigate its efficacy as a first line therapy even though it had a more favorable toxicity profile than sorafenib [89,90]. Moreover, another phase III, randomized, placebo-controlled study investigated the efficacy of brivanib after sorafenib failure and the authors reported that, in comparison to placebo, brivanib resulted in a longer median TTP but insignificant increase in the OS (Table 1) [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108].…”
Section: Anti-angiogenic Agentsmentioning
confidence: 99%
“…Essentially, pharmacodynamic studies showed that selumetinib was able to block MEK signal ing by preventing phosphorylation of ERK and MEK [101]. On the other hand, refametinib is a potent non-ATP competitive inhibitor of MEK 1 and MEK 2 [102]. Preclinical studies have demonstrated its activity as a single agent and in combination with sorafenib.…”
Section: Mapk Inhibitorsmentioning
confidence: 99%